2017
DOI: 10.15537/smj.2017.6.17190
|View full text |Cite
|
Sign up to set email alerts
|

High serum uric acid levels may increase mortality and major adverse cardiovascular events in patients with acute myocardial infarction

Abstract: Objectives:To determine the validity of uric acid as a potential prognostic marker for long-term outcomes of patients with acute myocardial infarction (AMI) and those with AMI undergoing percutaneous coronary intervention (PCI).Methods:Systematic review and meta-analysis were performed. We retrieved data from retrospective and prospective cohort studies that investigated whether serum uric acid (SUA) level affects the prognosis of patients with AMI.Results:Thirteen studies involving 9371 patients were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
2
12
0
1
Order By: Relevance
“…The prognostic role of uric acid level has been widely evaluated in patients with AMI. In line with our meta‐analysis, a previously well‐designed meta‐analysis has concluded that higher SUA level independently predicted the short‐term or mid/long‐term all‐cause mortality and MACEs in AMI patients. However, most of the included studies enrolled patients with ST segment elevated myocardial infarction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prognostic role of uric acid level has been widely evaluated in patients with AMI. In line with our meta‐analysis, a previously well‐designed meta‐analysis has concluded that higher SUA level independently predicted the short‐term or mid/long‐term all‐cause mortality and MACEs in AMI patients. However, most of the included studies enrolled patients with ST segment elevated myocardial infarction.…”
Section: Discussionsupporting
confidence: 90%
“…Lower excretion increased synthesis or both contribute to higher circulating uric acid level . Serum uric acid (SUA) level has been recognized as a prognostic biomarker in patients with acute myocardial infarction (AMI) . Findings from observational studies have linked the high SUA level and adverse prognosis in ACS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between SUA and CVD was first reported more than 50 years ago, and several epidemiological studies were conducted to assess the association between hyperuricemia (HU) and CVD [5]. Although many studies have been conducted assessing the relationship between UA and CVD, there is disagreement about this relationship [6]. These controversies are due to the dual effect of UA in the body [7].…”
Section: Introductionmentioning
confidence: 99%
“…Serum uric acid (SUA) has long been associated with dyslipidemia, diabetes, hypertension, coronary calcifications and renal failure [13]. It has been suggested that elevated SUA may be associated with mortality in high risk patients with asymptomatic carotid atherosclerotic disease, acute myocardial infarction, heart failure, diabetes mellitus and hypertension [47]. The role of SUA as an independent risk factor for CV mortality is questionable.…”
Section: Introductionmentioning
confidence: 99%